2015
DOI: 10.1021/acs.jafc.5b03221
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Rutin and Betulinic Acid and Expression of Phenylpropanoid and Triterpenoid Biosynthetic Genes in Mulberry (Morus albaL.)

Abstract: Mulberry (Morus alba L.) is used in traditional Chinese medicine and is the sole food source of the silkworm. Here, 21 cDNAs encoding phenylpropanoid biosynthetic genes and 21 cDNAs encoding triterpene biosynthetic genes were isolated from mulberry. The expression levels of genes involved in these biosynthetic pathways and the accumulation of rutin, betulin, and betulinic acid, important secondary metabolites, were investigated in different plant organs. Most phenylpropanoid and triterpene biosynthetic genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 35 publications
1
52
0
Order By: Relevance
“…After the initial screening by docking and fluorescence studies, role of two natural compounds rutin and vanillin as an inhibitor of MARK4 has been studied in detail. Rutin is a dietary flavonoid and vanillin is a phenolic aldehyde, both are present in our routine foodstuffs like citrus fruits and vegetables 22 , 57 , 59 . Here we investigate their role in MARK4 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial screening by docking and fluorescence studies, role of two natural compounds rutin and vanillin as an inhibitor of MARK4 has been studied in detail. Rutin is a dietary flavonoid and vanillin is a phenolic aldehyde, both are present in our routine foodstuffs like citrus fruits and vegetables 22 , 57 , 59 . Here we investigate their role in MARK4 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequence analysis of these two clones indicated a high level of homology (more than 80%) to known CHS family proteins isolated from other plant species ( Figure 4). Accordingly, Unigene15633 and CL3598 are designated as MaCHS4 and MaCHS5 respectively, because three other CHS genes (MaCHS1, MaCHS2, MaCHS3) have been described previously (Zhao et al, 2015).…”
Section: Cloning Genes Encoding Key Flavonoid Biosynthesis Enzymesmentioning
confidence: 99%
“…The above results showed that the UFGT gene was the key factor in isoquercitrin and astragalin biosynthesis in mulberry leaves, but not the key factor of rutin biosynthesis. Zhao et al [23] reported that flavonol-3-O-glucoside L-rhamnosyltransferase (UGT78D1) plays an important regulatory role in the rutin biosynthetic pathways in mulberry leaves (Morus alba L.), but UFGT is not the key enzyme. This conclusion can explain why the UFGT gene is not the key factor of rutin biosynthesis in mulberry leaves.…”
Section: Correlation Analysis Between Average Temperature and Expressmentioning
confidence: 99%